2020
DOI: 10.1002/anie.202012971
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Large Area Two‐Dimensional Metal–Organic Framework Films on Copper Anodes

Abstract: Owing to their excellent physical and electrical properties, metal–organic framework (MOF) materials with well‐defined supramolecular structures have received extensive research attention. However, the fabrication of large‐area two‐dimensional (2D) MOF films is still a significant challenge. Herein, we propose a novel electrochemical (EC) synthesis method for the preparation of large‐area Cu3(HHTP)2 MOF film on single‐crystal Cu (100) anode. The surface reaction was achieved via charge‐induced molecular assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 45 publications
(8 reference statements)
3
99
0
1
Order By: Relevance
“…Meanwhile, at the already nucleated sites, the MOFs are gradually growing into large ones with dimensions of several microns, and finally cover the whole conductive substrate to form a compact layer. Detachment: due to the uninterrupted release of metal ions from the anodic electrode, a lot of voids are formed between the MOF layer and the electrode surface, leading to the buckling of the MOF layer and finally resulting in the detachment. Besides, the formation of charged intermediates may also cause the occurrence of detachment due to the electrostatic repulsion (vide infra) 42 …”
Section: Mofsmentioning
confidence: 99%
“…Meanwhile, at the already nucleated sites, the MOFs are gradually growing into large ones with dimensions of several microns, and finally cover the whole conductive substrate to form a compact layer. Detachment: due to the uninterrupted release of metal ions from the anodic electrode, a lot of voids are formed between the MOF layer and the electrode surface, leading to the buckling of the MOF layer and finally resulting in the detachment. Besides, the formation of charged intermediates may also cause the occurrence of detachment due to the electrostatic repulsion (vide infra) 42 …”
Section: Mofsmentioning
confidence: 99%
“…Later on, similar conductivity values of Cu‐CAT (range from 0.002 to 0.04 S/cm) were obtained in several studies (Table 1). [62–64] Although, original study missed out on the electrical conductivity of Co and Ni congeners, it was found to be 0.1 to 1.6×10 −4 S/cm for Ni‐CAT [63,65–66] and 2×10 −3 to 2.7×10 −6 S/cm for Co‐CAT (Table 1) [63,65a,66a] in the succeeding works. Furthermore, less crystalline Fe 3 (HHTP) 2 was reported with 3×10 −3 S/cm conductivity [63] .…”
Section: Extended Conjugationmentioning
confidence: 99%
“…The flattened surface is conducive to grow Cu(OH) 2 NRs homogeneously. [25] Characterization of Cu(OH) 2 nanorods Figure 3(a) is the XRD pattern of Cu(OH) 2 NRs prepared by chemical oxidation method in the mixed solution of (NH 4 ) 2 S 2 O 8 and NaOH. The XRD peaks at ∼ 17°, ∼ 24°, ∼ 34°, ∼ 32°, ∼ 36°, ∼ 38°, and ∼ 40°, ∼ 47°, can be assigned to (020), ( 021), (002), (À 110), ( 111), ( 022), (130), and (À 202) crystal face, respectively, which are indexed to the orthorhombic Cu(OH) 2 .…”
Section: Characterization Of Single Crystal Cu Foilmentioning
confidence: 99%
“…Two characteristic peaks appeared at ∼ 935 eV and ∼ 955 eV are corresponded to Cu 2p 3/2 and Cu 2p 1/2 , respectively. [25,28] The satellite peak presented at 941-947 eV can be divided into electron-correlation effects of 3d 9 , which indicates the formation of Cu 2 + . In the Ni 2p region, two characteristic peaks seated at ∼ 854 eV and ∼ 872 eV are attributed to Ni 2p 3/2 and Ni 2p 1/2 , respectively.…”
Section: Characterization Of Cu(oh) 2 Nrs @ Ni(oh) 2 Nssmentioning
confidence: 99%